Endocrine Effects of Heat Stress in Boars - Larsson, K. (Acta Vet Scand, 1983)
The purpose of this study was to describe the temporal changes in peripheral plasma levels of testosterone and Cortisol in boars during and after heat stress. A total of 8 boars were utilized, 4 of them were exposed to 35°C, for 100 h in a climatic room, and 4 served as controls and were kept at 20 °C for 100 h in the climatic room. Blood samples were obtained via permanent vein catheters 3 times daily from 5 days before heat stress until 20 days after termination of heat stress. Testestorone levels were determined by radioimmunoassay and Cortisol by a competitive protein binding technique. For both hormones the pre-exposure levels were similar in both groups of boars. The control boars had significantly higher testosterone levels, while being in the climatic room, than during any other period. The experimental boars had slightly increased testosterone levels during the first day of heat stress and thereafter continuously decreased levels. In the control boars the testosterone levels returned to pre-exposure levels immediately after removal from the climatic room, whereas in the experimental boars the testosterone levels were dramatically increased during the first 5 days after exposure. The differences in Cortisol levels, between the 2 groups of boars were restricted to the period spent in the climatic room. During this period the experimental boars had significantly higher Cortisol levels.